المحاسبة عن الأدوات المالية بين النظام المحاسبيالمالي ومعايير الإبلاغ المالي الدولية "دراسة مقارنة مجموعة مؤسسات محلية وأجنبية" - سعيد نورالدين (My University, 2024)
الملخص: تهدف الد ا رسة إلى التعرف على محاسبة الأدوات المالية وفق معايير الإبلاغ المالي الدولي والمقارنة بينهما، وذلك من خلال عرض الأدوات المالية )SCF( والنظام المحاسبي المالي IAS/IFRS والمحاسبة عنها لمجموعة من الشركات المدرجة في بورصة الكويت، وكذا مجموعة من المؤسسات المدرجة بغرض الوقوف على نقاط التشابه والإختلاف - في البورصة الج ا زئرية خلال الفترة الممتدة 2020- 2022 بينهم. IAS توصلت الد ا رسة إلى أن الشركات المدرجة في بورصة الكويت تطبق متطلبات المعيارين الذي تم إلغاءه وباشرت في )IAS وتخلت عن تطبيق المعيار المحاسبي الدولي 39 IFRS 32 و 07 المستحدث، في حين أن المؤسسات الج ا زئرية ما ا زلت )IFRS تطبيق معيار الإبلاغ المالي الدولي ) 09 تعتمد في محاسبتها عن الأدوات المالية على متطلبات المعيار الملغى، مما يستوجب تحيين النظام المحاسبي المالي الج ا زئري ليواكب مستجدات معايير الإبلاغ المالي الدولية. ------------ Summary: The study aims to identify the accounting for financial instruments according to International Financial Reporting Standards (IAS/IFRS) and the Financial Accounting System (SCF), and to compare between them, by presenting financial instruments and their accounting for a group of companies listed on the Kuwait Stock Exchange, as well as a group of institutions listed on the Algerian Stock Exchange during the period (2020-2022), in order to identify points of similarity and difference between them. The study concluded that companies listed on the Kuwait Stock Exchange apply the requirements of standards (IAS 32) and (IFRS 07), and have abandoned the application of the International Accounting Standard (IAS 39) which has been abolished and started applying the newly introduced International Financial Reporting Standard (IFRS 09), while Algerian institutions still rely on the requirements of the abolished standard in their accounting for financial instruments, necessitating the updating of the Algerian financial accounting system to keep pace with developments in international financial reporting standards. ----------- Résumé : L'étude vise à identifier la comptabilité des instruments financiers conformément aux normes internationales d'information financière (IAS/IFRS) et au système comptable financier (SCF), et à les comparer, en présentant les instruments financiers et leur comptabilité pour un groupe d'entreprises cotées à la Bourse du Koweït, ainsi qu'un groupe d'institutions cotées à la Bourse d'Algérie pendant la période (2020-2022), afin d'identifier les points de similitude et de différence entre eux. L'étude a conclu que les entreprises cotées à la Bourse du Koweït appliquent les exigences des normes (IAS 32) et (IFRS 07), et ont abandonné l'application de la norme comptable internationale (IAS 39) qui a été abolie et ont commencé à appliquer la nouvelle norme internationale d'information financière (IFRS 09) introduite, tandis que les institutions algériennes continuent de s'appuyer sur les exigences de la norme abolie dans leur comptabilité des instruments financiers, ce qui nécessite la mise à jour du système comptable financier algérien pour suivre les évolutions des normes internationales d'information financière.
Keywords: أدوات مالية، بورصة، محاسبة الأدوات المالية، معايير الإبلاغ المالي الدولي، النظام المحاسبي المالي.; financial instruments; stock exchange; accounting for financial instruments; International Financial Reporting Standards; financial accounting system; instruments financiers; bourse; comptabilité des instruments financiers; normes internationales d'information financière; système comptable financier.